Penilaian Kemandirian Belajar Matematika Madrasah Tsanawiyah - Hartini, Sri; Sumardi, S. (Manajemen Pendidikan, 2018)
The purpose of this study is to describe the assessment of self-reliance learning mathMTs. This research method using qualitative method by using holistic research design.Techniques of data collection using observation, interviews, and documentation. Thisresearch uses interactive analysis model. The results of this study are: Assessmentof learning independence in MTs mathematics learning, conducted by the head ofthe madrasah along with the board of teachers at the regular meeting monthly, semester, semester and year. observations were recorded in the student developmentobservation journal.